(untitled) (Journal of the College of Basic Education, 2023)
The current research aims to identify the mutual social trust of kindergarten teachers, where the two researchers adopted the Roter scale (Rotter, 1967), and the scale in its final form consisted of (25) items applied to a sample consisting of (150) kindergarten teachers in the General Directorate of Education The second Rusafa, which was chosen randomly, and its validity and reliability were verified by extracting the validity by the apparent honesty method and the constructive validity. As for the reliability, it was extracted by the re-test method and the Wackeronbach coefficient, and the results concluded that the research sample members have mutual social trust.Keywords: mutual social trust, kindergarten teachers.